2015
DOI: 10.7307/ptt.v27i3.1551
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Neural Network Model for Highway Accident Prediction: A Case Study of Erzurum, Turkey

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 20 publications
0
36
0
1
Order By: Relevance
“…ANNs was also applied to determine the relationship between crash severity and the model parameters including years, highway sections, section length (km), AADT, the degree of horizontal curvature, the degree of vertical curvature, heavy vehicles (percentage), and season summer (percentage). The results shown that degree of vertical curvature has strong impact on number of crashes [28]. By modeling AADT, SL (Posted speed limit), Gradient (Average segment gradient), and Curvature (Average segment curvature) against road crashes, it was concluded that ANN was superior to multivariate Poisson-lognormal models [29].…”
Section: Anns For Road Safety Analysismentioning
confidence: 97%
“…ANNs was also applied to determine the relationship between crash severity and the model parameters including years, highway sections, section length (km), AADT, the degree of horizontal curvature, the degree of vertical curvature, heavy vehicles (percentage), and season summer (percentage). The results shown that degree of vertical curvature has strong impact on number of crashes [28]. By modeling AADT, SL (Posted speed limit), Gradient (Average segment gradient), and Curvature (Average segment curvature) against road crashes, it was concluded that ANN was superior to multivariate Poisson-lognormal models [29].…”
Section: Anns For Road Safety Analysismentioning
confidence: 97%
“…Much of the recent work in this field focuses on enhancement techniques and methods of increasing the signal-to-noise ratio [14][15][16][17]. Methods like linear regression, logic regression model, Poisson model and negative binominal model are subject to strong assumption and limitations in applications [18]. Some methods are more commonly used; however, this does not state its accuracy in prediction.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Çodur, yapay sinir ağları yöntemini kullanarak Erzurum ili karayolu trafik kazalarının analizini yapmıştır. Yapay sinir ağları ile yapılan analizlerde karayolu trafik kazalarında en etkili parametrenin düşey kurblar olduğu tespit edilmiştir [34]. Akgüngör ve Doğan; regresyon analizi, yapay sinir ağları ve genetik algoritma yöntemlerini kullanarak İzmir ili için trafik kaza tahmin modelleri geliştirmişlerdir.…”
Section: Ftunclassified